MR Imaging of the Intraparotid Facial Nerve: Normal Anatomy and Pathology - Teresi, Louis M.; Kolin, Elliot; Lufkin, Robert B.; Hanafee, William N. (American Journal of Neuroradiology, 1987)
Three normal volunteers, 58 normal patients, and three patients with parotid tumors were studied with a 0.3 T permanent-magnet imaging system to directly image the intraparotid facial nerve. On T1-weighted images the nerve appeared as a curvilinear structure of relatively low signal intensity within the fatty, high-signal parotid parenchyma. Its major divisions and branches could be imaged only with specially angled axial scan planes. To verify our observations MR imaging was compared with whole-organ cryomicrotome sections cut at the same angles. Normal variations in the appearance of the nerve and pitfalls in its visualization are discussed. Three cases of parotid tumors, with surgical confirmation of the relationship of the facial nerve to the tumor, are presented. MR is the only imaging technique capable of direct imaging of the facial nerve in the parotid bed: it may assist materially in the surgical management of tumors of the parotid gland.